Lived experiences of married men whose HIV positive pregnant spouses are enrolled in PMTCT programme at Dedza district hospital. - M'baya, Beatrice (Kamuzu University of Health Sciences, 2022)
HIV can be transmitted from mother to child during antenatal period, child birth and postnatally during breastfeeding. This can be prevented through PMTCT services which can be initiated either antenatally or postnatally. The purpose of this study is to explore the experiences of men whose HIV+ pregnant spouses are enrolled in PMTCT programme at antenatal clinic, to assess their perceptions towards this programme and to make recommendations on the strategies that can be put in place to facilitate the utilization of PMTCT services and to promote male involvement. The study will be guided by Family Centred Model and Health Belief Model. Ten men would be followed up through their HIV+ pregnant women who are enrolled in PMTCT programme and would be identified at the antenatal clinic. A qualitative study design will be used. Data will be collected through an interview and using questionnaire then will be analysed manually. The research will be conducted at Dedza District Hospital located in the central region of Malawi, where 200-300 women attend antenatal services almost daily, but less than 10 women are accompanied by their husbands and about three men accept to be tested and get the results. Ethical consideration will be observed, thus consent from the participants and permission from the heads of department will be respected and followed.